Pengaruh Persentase Arang Tempurung Kemiri Terhadap Nilai Kalor Briket Campuran Biomassa Ampas Kelapa - Arang Tempurung Kemiri - Gde Gianyar, Ida Bagus; Nurchayati, Nurchayati; Padang, Yesung Allo (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2012)
Indonesia has many sources of renewable energy. One of the source  renewable energy in Indonesia is biomass, because the price of biomass is relatively cheap and so far abundant numbers. Coconut dregs and hazelnut shell are biomass where these can’t be utilized optimally. Biomass can be made into briquettes which is a fuel with high calorific value.            The method used in this study is an experimental method. Begining the process with manufacture of briquettes which is the drying process of coconut dregs and hazelnut shell using the sun until dry, then the process of composing hazelnut shell. Raw materials crushed and sieved, after that the raw material made into briquettes by varying the percentage composition of coconut dregs and charcoal hazelnut shell as follows 80% : 20%, 60% : 40%, 40% : 60%, 20% : 80%. Then, the briquettes are tested their calorific value and moisture content.            The results show that higher heating value (HHV) and lower heating value (LHV) are the highest in the mix of AK 20% : ATK 80% is equal to 34,517 kJ/gr (8.242,819 cal/gr) and 34,172 kJ/gr (8.160,523 cal/gr). Meanwhile the briquettes moisture content range between 2,474% - 3,186% with average of 2,836%. In term of calorific value and moisture content, biomass briquettes from coconut dregs and charcoal hazelnut shell meets the quality standards set by the standards of Indonesia, Britain, Japan and USA.